A solution for the management of multimedia sessions in hybrid clouds. (1st January 2014) - Dutu, Cristina; Apostol, Elena; Leordeanu, Catalin; Cristea, Valentin
Cloud-based systems expanded considerably in recent years, as the demand for cheaper and easily scalable resources provisioning solutions increased. In this context, the deployment of multimedia services in the cloud, as a way to increase their usability and overcome their processing overhead, gained additional interest. Throughout this paper we present the design of a management system for multimedia services built on top of a hybrid cloud. This describes a model of service unit deployment automation as well as a services composition scheme adapted to the IaaS cloud architecture and resources pool. We propose a modular and flexible architecture to handle service composition, automated service deployment with execution flow management and scalable storage capabilities. Finally we analyse the benefits of using the service management system with a hybrid cloud back-end.